Test results comparison and sample stability study is the BD Barricor tube a suitable replacement for the BD RST tube? - Mandić, Sanja, biokemičarka; Mandić, Dario; Lukić, Iva; Rolić, Tara; Horvat, Vesna, biokemičarka; Lukić, Maja, biokemičarka; Osvald, Silvija; Šerić, Vatroslav, medicinski biokemičar (2020)
Introduction: The aim was to evaluate the BD Barricor tubes by comparison with the BD Rapid Serum Tubes (RST) through measuring 25 analytesand monitoring sample stability after 24 hours and 7 days.Materials and methods: Samples of 52 patients from different hospital departments were examined. Blood was collected in BD RST and BDBarricor tubes (Becton, Dickinson and Company, Franklin Lakes, USA). Analytes were measured by Beckman Coulter AU 480 (Beckman Coulter, Brea,USA), Dimension EXL (Siemens Healthcare Diagnostics, Newark, USA) and ARCHITECT i2000SR (Abbott Diagnostics, Lake Forest, USA). Between-tubecomparison for each analyte was performed, along with testing analyte stability after storing samples at 4 °C.Results: BD Barricor tubes showed unacceptable bias compared to BD RST tubes for potassium (K) (- 4.5%) and total protein (4.4%). Analyte stabilityafter 24 hours was acceptable in both tested tubes for most of analytes, except for glucose, aspartate aminotransferase (AST) and lactate dehydrogenase(LD) in BD Barricor and free triiodothyronine in BD RST sample tubes. Analyte stability after 7 days was unacceptable for sodium, K, calcium,creatine kinase isoenzyme MB, AST, LD and troponin I in both samples; additionally for glucose, alkaline phosphatase and albumin in BD Barricor.Conclusion: All analytes, except K and total protein, can be measured interchangeably in BD RST and BD Barricor tubes, applying the same referenceintervals. For most of the analytes, sample re-analysis can be performed in both tubes after 24 hours and 7 days, although BD RST tubes show better7-day analytes stability over BD Barricor tubes.
Bibliografija: 21 jed.
Summary.
Keywords: BD-Barricor epruvete -- Serum -- Plazma -- Stabilnost -- Ocjenjivanje